Preliminary results of a physiologically based treatment of amblyopia. Issue 11 (November 1978) - Campbell, F. W.; Hess, R. F.; Watson, P. G.; Banks, R.
Abstract : An apparatus has been developed in which high-contrast square-wave gratings are rotated in front of the amblyopic eye while the child is performing some task requiring visual concentration. In the course of three 7-minute treatments 73% of patients treated achieved 6/12 or better; 75% of these patients had previously undertaken conventional or minimal occlusion.